The Emerging Role of Triggering Receptor Expressed on Myeloid Cells 2 as a Target for Immunomodulation in Ischemic Stroke - Gervois, Pascal; Lambrichts, Ivo (Frontiers in Immunology, 2019)
Stroke is the second most common cause of death and permanent disability. It is characterized by loss of neural tissue in which inflammation plays a crucial role in both the acute contribution to ischemic damage as in the late-stage impact on post-ischemic tissue regeneration. Microglia play a key role in the inflammatory stroke microenvironment as they can adapt a disease-promoting pro-inflammatory- or pro-regenerative phenotype thereby contributing to the exacerbation or alleviation of ischemic damage respectively. Triggering receptor expressed on myeloid cells 2 (TREM2) is a cell surface receptor which in the central nervous system is mainly expressed on microglia. This receptor has been shown to play an essential role in microglial phagocytosis and function but its contribution in stroke pathobiology remains unclear. TREM2 was shown to be activated by nucleotides and lipid mediators, key factors that are secreted in the extracellular stroke environment by apoptotic neurons and cell/myelin debris. These factors in turn stimulate TREM2 signaling which mediates microglial migration towards- and phagocytosis of myelin debris and apoptotic cells. Moreover, microglial TREM2 appears to counteract the toll-like receptor response, thereby decreasing the production of pro-inflammatory cytokines. Finally, TREM2 is involved in microglial migration, survival, and is suggested to directly stimulate pro-regenerative phenotype shift. Therefore, this receptor is an attractive target for microglial modulation in the treatment of ischemic stroke and it provides additional information on microglial effector functions. This short review aims to elaborate on these TREM2-mediated microglial functions in the pathobiology and resolving of ischemic stroke.